Problems in the Implementation of K-12 Curriculum by Grade 11 Students in Aurora Province, Philippines - Barcelo, Cris Dan (JPAIR Institutional Research, 2019)
The K-12 Curriculum is implemented in the Philippines through the virtue of the Republic Act 10533. The new curriculum covers Kindergarten and 12 years of basic education: six years of primary education, four years of Junior High School (JHS), and two years of Senior High School (SHS). Due to abrupt changes in the curriculum, this resulted in different problems which may experience by the students. This research used both descriptive and inferential research design to identify the degree of problems encountered by 364 students. Suggestions of the students based on the problems were also collected together with the relationship of students’ profiles to the different problems identified. Data from the survey questionnaire regarding the degree of problems were subjected to a weighted mean and the relationship of variables were determined through a chi-square test. The study revealed that curriculum implementation caused many problems. Classrooms, tables, chairs, books, a specialized teacher in major subjects, computer laboratory, audio-visual instrument, laboratories, Tech-Voc equipment, tuition fees, home distance to school, and financial matters were enumerated by the students as serious problems (Grand Mean= 3.33). A significant asymptotic value of 0.007 showed that the monthly family income of the students has a significant relationship to the different problems. Findings concluded that as the family income decreases, problems encountered by the students become more serious.
Keywords: Education; K to 12 Curriculum; descriptive and inferential research design; Philippines